AZETIDIN-2-ONE FUSED QUINOLINE ANALOGUES: SYNTHESIS AND BIOLOGICAL EVALUATION OF SOME NOVEL 2-CHLORO-3-FORMYL QUINOLINE DERIVATIVES - Nayak, Govind; Shrivastava, Birendra; Singhai, Akhlesh Kumar (International Journal of Current Pharmaceutical Research, 2016)
Objective: The aim of the present invention is to synthesize and find out the biological significance of the series of the designed azetidin-2-one fused 2-chloro-3-formyl quinoline derivatives. Methods: A new series of 2-chloro-3-formyl quinolines derivatives 3-chloro-4-(2-chloro-8/7/6-methoxyquinolin-3-yl)-1-phenyl amino)azetidin-2-one, 3-chloro-4-(2-chloro-8/7/6-chloroquinolin-3-yl)-1-(phenylamino) azetidin-2-one, 3-chloro-4-(2-chloro-8/7/6-methylquinolin-3-yl)-1-(phenyl -amino)azetidin-2-one were synthesized by four steps. The cyclization is facilitated by N-aryl acetamides bearing electron donating groups at ortho-position. However yields of quinolines having electron donating groups in all cases. The structures of the synthesized compounds have been established on the basis of physical and spectral data and are screened for diuretic, some of the exhibited significant activity. Results: The moderate yield of the proposed compounds was obtained. Spectral analysis and physical characteristic showed that the structural confirmation of the quinoline derivatives of the synthesized compounds. Some of the compounds showed lower to moderate level of significant activities. Conclusion: From the result of spectral data and diuretic activity it has concluded that the compounds were found to exhibited significance activity.